Climate change effects on rangelands and rangeland management: affirming the need for monitoring. Issue 3 (29th March 2017) - McCollum, Daniel W.; Tanaka, John A.; Morgan, Jack A.; Mitchell, John E.; Fox, William E.; Maczko, Kristie A.; Hidinger, Lori; Duke, Clifford S.; Kreuter, Urs P.
Abstract: Uncertainty as to the extent and magnitude of changes in conditions that might occur due to climate change poses a problem for land and resource managers as they seek to adapt to changes and mitigate effects of climate variability. We illustrate using scenarios of projected future conditions on rangelands in the Northern Great Plains and Desert Southwest of the United States. These two regions are different in the ways climate change is projected to affect the regions. Projection of a longer and warmer growing season in the Northern Great Plains could lead to increased forage production and land productivity. Highly uncertain effects on summer monsoons that primarily control rangeland productivity in the Desert Southwest, combined with the possibility of more intense and/or frequent drought events, could present land managers with challenges stemming from decreased forage production and land productivity. Climate projections, though uncertain, provide land managers with basic insight into future conditions they might encounter. They need more. A focus on vulnerability and resilience, with explicit recognition of interactions between ecological and socio‐economic factors, coupled with systematic monitoring and assessment of observable conditions on the land to supplement information based on climate projections, will more effectively provide critical and specific information managers need to adaptively manage rangelands under uncertain climate futures.